Immunostimulatory effects of Uncaria perrottetii (A. Rich) Merr. (Rubiaceae) vinebark extract In Vivo - Nudo, Leonora P. (Transactions of the National Academy of Science and Technology, 2011)
The immunostimulatory effects of Uncaria perrottetii (A. Rich) Merr. Vinebark aqueous extract was evaluated by employing a number of immune response assays in vivo. Initially, the optimum concentration was determined in vitro to be 50µg/mL. This concentration was then assessed for the immunoprotective effects of the extract against immunosuppressed Balb/C mice. Thirty-six (36) mice were divided into 3 groups: (1) Phosphate buffered saline (PBS)-injected mice; (2) U. perrottetii extract and Cy-treated mice (U+Cy); and (3) cyclophosphamide (Cy)-induced immunosuppressed mice. Group 1 was injected intraperitoneally with 0.2mL of 30mg/kg body weight of cyclophosphamide (Endoxan) at days 1, 4, 7 and 10 of the treatment period. Cyclophosphamide was also administered to group 2 one hour after each administration of the plant extract. 50mL/kg body weight of PBS and U. perrottetii extract (2.5 mg/kg body weight) was administered daily. In all immune assays undertaken, group 3 showed significantly lower response when compared with group 1. Group 2 showed significant improvement in phagocytic activity (27%), proliferation of cells with (29.61%) and without (44.57%) lipopolysaccharide, superoxide production (P<0.05), and plasma lysozyme activity (P<0.05) compared with the group 3. The study showed that the extract could potentially reverse the immunosuppressive effects of cyclophosphamide in vivo. There is, therefore, a great potential of the plant as a source of bioactive products and metabolites for drug development.